From a Barrio Chino Urban Stigma to the Raval Cultural Brand: Urban Memory and Cultural Policies in the Renewal of Central Barcelona. (November 2022) - Rius-Ulldemolins, Joaquim; Klein, Ricardo
Barcelona, and especially, its historic center, has undergone a profound transformation from an industrial city to a global tourism and services center. Some authors insist on the destructive nature of the urban regeneration of the historic Barcelona district of Raval as a process of de-identification of the city center or as an intentional falsification of its identity to turn it into a tourist space. However, as we discuss in this article, urban branding and urban change projects should address not only the infrastructural issues of transformation, but also the development of new urban branding based on recreating a memory of the place. Thus, in the case of Raval, the urban and cultural planning led by the local government and the development of cultural institutions took place as part of the construction and revitalization of the identity of the neighborhood from that of a barrio chino red-light district stigma to one of a new cultural quarter.